PEMANFAATAN MINYAK BERAT HASIL PERENGKAHAN KATALITIK MINYAK PLASTIK POLYPROPYLENE-LOW DENSITY POLYETHYLENE UNTUK MENINGKATKAN KUALITAS LIGNIT - Marlinda, Lenny; Mardhatillah; Raden Ilham; Rahmi; Muhammad Al Muttaqii (Balai Besar Pengujian Mineral dan Batubara tekMIRA, 2024)
The most obvious characteristics of lignite are its high moisture content (30-50%) and relatively low calorific value compared to other types of coal. This causes low combustion efficiency, making it not optimal for use as fuel. In this study, the slurry dewatering process was applied to coal that has a low calorific value of 3,662 cal/g and a moisture content of 37.29%. The addition effect of heavy oil from catalytic cracking of Polypropylene-Low Density Polyethylene (PP/LDPE) plastic waste pyrolysis oil on improving quality of lignite was investigated in this study. Heavy oil was used as additive. The ratio of 120 mesh lignite to heavy oil used was 100:15, 100:30, 100:45, 100:60, 100:75, and 100:90 (g/mL). Coal was carried out with a slurry dewatering process in an autoclave at various temperatures of 140 and 150 °C for 60 min. The test results obtained the highest calorific value of 6,374 cal/g and the moisture content of 2.81% for a ratio of lignite to heavy oil of 100: 45 g/mL at a temperature of 140 °C.